2003
DOI: 10.1592/phco.23.15.1617.31958
|View full text |Cite
|
Sign up to set email alerts
|

Fenoldopam and N‐acetylcysteine for the Prevention of Radiographic Contrast Material—Induced Nephropathy: A Review

Abstract: Radiographic contrast material-induced nephropathy (RCIN) is the third most common cause of hospital-acquired renal insufficiency and has been associated with an increase in patient mortality. Many strategies to prevent RCIN have been explored unsuccessfully. The standard of care remains hydration with 0.45% sodium chloride before and after administration of contrast material. Recently, N-acetylcysteine and fenoldopam have been studied to determine their efficacy in preventing RCIN. Of seven prospective studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In these trials, N-acetylcysteine was given in addition to the general hydration protocols and showed a positive outcome in four of the studies [44,45,47,49] and has therefore been recommended for the prevention of CIN in patients with mild-to-moderate renal insufficiency [50][51][52]. However, this recommendation is not unequivocal since other trials fail to confirm a positive effect [48,53] or indicate that rigorously controlled larger trials are still required [54].…”
Section: Altered Mitochondrial Function In a Proximal Tubular Cell mentioning
confidence: 99%
“…In these trials, N-acetylcysteine was given in addition to the general hydration protocols and showed a positive outcome in four of the studies [44,45,47,49] and has therefore been recommended for the prevention of CIN in patients with mild-to-moderate renal insufficiency [50][51][52]. However, this recommendation is not unequivocal since other trials fail to confirm a positive effect [48,53] or indicate that rigorously controlled larger trials are still required [54].…”
Section: Altered Mitochondrial Function In a Proximal Tubular Cell mentioning
confidence: 99%
“…Its clinical uses range from mucolytic therapy for patients with inspissated respiratory secretions to standard treatment of acetaminophen overdoses (21). Recently, NAC has also been used for the prevention of contrast-induced nephropathy (22,23). The efficacy of NAC may be secondary to detoxification of OFR, local vasoactive properties, or interference with gene expression (16,20).…”
Section: Introductionmentioning
confidence: 99%
“…NAC is a well known amino thiol molecule with clinical uses ranging from mucolytic therapy for patients with inspissated respiratory secretions to standard treatment of acetaminophen overdoses 13) and more recently for the prevention of contrast-induced nephropathy. 14) NAC partly acts as a free radical scavenger as well as a GSH precursor to increase intracellular antioxidant capacity and hence protect cells against ROS. 15) However, it is also thought to work through other mechanisms.…”
mentioning
confidence: 99%